ANALISIS PENGARUH RASIO ASSET TURNOVER DAN RASIO PROFITABILITAS TERHADAP RETURN SAHAM PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK PADA TAHUN 2012– 2016 - Ragil Ayu Setyaningrum; Subagyo Subagyo; Wahyu Suhardono (CAHAYA AKTIVA, 2019)
This study was made with the aim to determine the effect of Asset Turnover ratio, profitability on stock returns on mining companies listed on the Indonesia Stock Exchange. So that it is expected that the results of elite pension can contribute to mining companies especially in taking a policy. Data analysis techniques in this study using Multiple Regression Analysis,  Determinant Coefficients, Simultaneous Test (F), Partial Test (T). The population in this study is 9 mining companies that have financial data during 2012-2016. The results of this study indicate that: Partially the activity ratio has no effect on stock returns, partially profitability ratios have a significant effect on stock returns and simultaneously activity ratios and profitability ratios affect the stock returns of mining companies listed on the stock exchange in 2012-2016. Keywords:  Asset Turnover Ratio, Profitability, and Stock Return.